Wave-absorbing material

By using cobalt-iron-based energetic metal-organic complexes (CoFe-MOF) to prepare nano/micron porous composite powders and mixing them with paraffin or epoxy resin, the low-frequency and high-frequency absorbing properties of existing absorbing materials are solved. To solve the problem of deficiencies, we have achieved an absorbing material with excellent absorbing performance in a wide frequency band of 3-5GHz and 11.36GHz.

CN119331380APending Publication Date: 2025-01-21TAIYUAN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311449577.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-11-02
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The absorbing performance of existing absorbing materials in the low and high frequency bands has not reached the ideal level, especially in the band below 8GHz, there are few researches, and the performance of the C, S, L, X, and Ku bands still need to be promote.

Method used

Using cobalt-iron-based energetic metal-organic complexes (CoFe-MOF) as the precursor, nano/micron-scale porous composite powder is prepared through explosive decomposition and segmented calcination processes, and mixed with paraffin or epoxy resin to form an absorbing material . This method provides wave absorption performance with a reflection loss of about -30dB in the 3-5GHz range, and reaches a minimum reflection loss of -77.84dB at the high frequency band of 11.36GHz and a thickness of 2.03mm, with a bandwidth of 3.7GHz.

Benefits of technology

It achieves excellent absorbing performance in both low-frequency and high-frequency bands, enriches the types of absorbing materials in the low-frequency band, and significantly improves the absorbing performance in the high-frequency band.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004528622750000011
    Figure HDA0004528622750000011
  • Figure HDA0004528622750000012
    Figure HDA0004528622750000012
  • Figure HDA0004528622750000013
    Figure HDA0004528622750000013
Patent Text Reader

Abstract

The invention belongs to the technical field of wave-absorbing materials. The wave-absorbing material is specifically a ferrocobalt-based energetic metal organic complex. The wave-absorbing material comprises powder (also called CoFe-X) and an organic binder, the powder is obtained by calcining CoFe-MOF ({[CoFe3O4 (tza) 6 (H2O) 3] (NO3) 3.5 H2O} n) to explode, the weight ratio of CoFe-X to the organic binder is 1: 1, and the organic binder is paraffin or epoxy resin used as a wave-transmitting material. The corresponding reflection loss of the wave-absorbing material is about-30dB when the wave-absorbing material is in the range of 3-5GHz and the thickness is 4-5.5 mm, and the wave-absorbing material reaches the minimum RL value of-77.84 dB and the bandwidth of 3.7 GHz at the high frequency band of 11.36 GHz and the thickness of 2.03 mm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of wave absorbing materials, and more specifically to the wave absorbing material of the present application, a cobalt-iron-based energetic metal-organic complex. Background Art

[0002] Absorbing materials are functional materials that can absorb or significantly attenuate the electromagnetic energy of electromagnetic waves entering them, thereby reducing electromagnetic interference. With the rapid development of wireless communications, electromagnetic waves (EMW) have brought convenience to human life and production, but have also brought many adverse effects on the ecological environment, human health and military fields. The operating frequencies of various radio frequency devices and household appliances in life are almost all in the low frequency band of 1-4GHz. The corresponding ranges of the Ku, X, C, S, and L bands of radar operating frequencies are 12-18GHz, 8-12GHz, 4-8GHz, 2-4GHz, and 1-2GHz, respectively. According to the above requirements, it can be seen that the application ranges of different frequency bands are different, but no matter which application field, "thin thickness, light weight, strong absorption, and wide effective absorption band" are pursued by all excellent absorbing materials.

[0003] The strength of the wave absorption performance is related to the impedance matching and attenuation constant. The calculation formula of reflection loss (RL) is as follows: RL = 20log 10 |(Z0-Z in ) / (Z0+Z in )|, and the smaller the RL value, the better the wave absorption performance; the impedance matching|Z in / Z0|=|(μ r / ε r ) 1 / 2 tanh{j(2πfd / c)(μ r / ε r ) 1 / 2}|.

[0004] In the prior art, Pan et al. [1] We report a simple route to synthesize tunable Co-NPs embedded in porous nitrogen-doped carbon (Co / NC) nanorods via direct pyrolysis of bimetallic organic framework (CoZn-ZIF) precursors. 2+ The content and distribution of Co-NPs in the composite absorber change accordingly. 2+ and Zn 2+ When the molar ratio of carbonized composites is 3:1, the carbonized composites show the largest specific surface area and the best EMW absorption performance. When the filler mass loading is only 15wt%, the minimum reflection loss (RL min) reaches -52.3dB at 10.1GHz. A maximum effective absorption bandwidth (EAB, RL≤-10dB) of 5.0GHz (11.1-16.1GHz) was achieved in a 2.0mm thick sample. The total effective absorption bandwidth can reach 14.5GHz (3.5-18.0GHz) in the matching thickness range of 1.0mm to 5.5mm. Enhanced conductive / magnetic losses, strong interface / dipole / defect polarization, hierarchical pore structure and geometric effects give Co / NC absorbers improved impedance matching and enhanced electromagnetic wave attenuation.

[0005] In the prior art, Yu et al. [2] Cubic hollow CoNi / C composites were prepared by in-situ pyrolysis of ZIF-67. By controlling the pyrolysis process, CoNi nanoparticles were uniformly distributed in the N-doped porous carbon matrix. The composite has a unique hollow structure, high porosity, dual loss mechanism and abundant functional groups, and has excellent electromagnetic wave absorption performance. When the matching thickness is 3.9mm, the optimal reflection loss (RL) value can be as low as -61.8dB, and the effective absorption bandwidth can reach 10.2GHz (from 7.8 to 18GHz), covering the entire X-band (8-12GHz) and Ku-band (12-18GHz).

[0006] The existing technology is strong [3] It has been successfully prepared by in-situ derivatization from a metal organic framework Prussian blue, by controlled high temperature pyrolysis. Nanocubic Fe / C was obtained, which is actually composed of amorphous carbon with a cubic framework and uniformly dispersed core-shell structure Fe@graphitized carbon nanoparticles. Within the pyrolysis temperature studied (600-700℃), the structure, iron content, magnetic properties and degree of graphitization of the porous Fe / C nanocubes can be well adjusted. The minimum reflection losses at 600℃ and 650℃ are -22.6dB at 15.0GHz and -20.3dB at 13.5GHz, respectively, and their bandwidths below -10dB (90% absorption) are 12.7-18.0 and 10.8-18.0GHz, respectively. When the pyrolysis temperature reaches 700℃, the minimum reflection loss of Fe / C -10.6dB is reached at 10.5GHz. The increase in the graphitization degree of the amorphous carbon framework and graphite shell leads to an increase in the complex dielectric constant and dielectric loss characteristics. The uniform chemical composition and microstructure are conducive to the loss of electromagnetic waves through various polarization processes. The synergistic effect of dielectric loss, magnetic loss, and good impedance matching jointly attenuates electromagnetic waves.

[0007] In the prior art, Ouyang et al. [4]Using FeCoNi-based MOF-74 (FeCoNi-MOF) as a precursor, hollow sphere trimetallic microwave absorbers were obtained by high-temperature carbonization, and the effects of different carbonization conditions on the microwave absorption properties of the materials were studied. FeCoNi-MOF-74 annealed at 700°C exhibited excellent microwave absorption capabilities, with an RL value of -64.75 dB at 15.44 GHz, corresponding to the practical application thickness of the absorber (only 2.1 mm), and a minimum RL value of -69.03 dB at 5.52 GHz. In addition, the prepared samples can fully cover the Ku-band and X-band at 2.1 and 3.1 mm, respectively. When the absorber thickness is 2.47 mm, the maximum EAB reaches 8.08 GHz (9.92-18 GHz). This remarkable absorption performance is attributed to the synergistic effect between multiple loss mechanisms, while the hollow sphere morphology improves the impedance matching characteristics.

[0008] In the prior art, Wei et al. [5] Magnetic CoFe alloy @ nitrogen deposited carbon shell (CoFe@NC) was prepared by thermal decomposition of metal organic complex CoFe Prussian blue analog, and the composites with strong absorption, thin thickness and wide bandwidth were obtained. The annealing temperature has a significant effect on the dielectric and magnetic behavior of the composites, thus affecting the impedance matching and absorbing ability. The CoFe@NC composite obtained at 600℃ showed the best absorbing performance with an RL value of -50.77dB and a maximum EAB of 7.2GHz (2.1mm). This CoFe@NC composite has excellent absorbing performance, which is due to the high dielectric loss generated by the nitrogen-doped carbon as the shell and the high magnetic loss and conduction loss generated by the CoFe alloy as the core. The excellent absorbing properties of CoFe@NC composites make them ideal candidates for efficient microwave absorption applications.

[0009] The application of carbon-based materials in microwave absorption (MA) is limited due to the impedance mismatch caused by high dielectric constant and low magnetic permeability. Yang et al. [6] Cu@NPC, obtained by pyrolysis of copper-based MOFs at 700℃, was synthesized by a simple method, with an RL value of -41.5dB at 1.91mm. The composite material derived from Cu@NPC after HF treatment and calcination at 200℃ was Cu2O@nanoporous carbon (Cu2O@NPC). Variation of C and Cu2O content in Cu2O@NPC can adjust the dielectric constant and permeability, resulting in excellent ultra-wideband absorption bands. The minimum reflection loss (RL) of Cu2O@NPC-4 at 5.6GHz and 4.00mm is as high as -31.1dB, while the effective bandwidth with a matching thickness of 1.85mm can reach 7.3GHz (10.7-18GHz).

[0010] It can be seen that the carbon composite materials derived from the pyrolysis of MOFs as precursors are diverse and their absorption mechanisms are complicated.

[0011] There are many methods for preparing nanomaterials, such as aerosol-gel method, microemulsion method, precipitation method and other chemical production methods. Among them, the explosion method has the advantages of high product purity, rapidity and convenient parameter adjustment. Explosion synthesis mainly includes detonation chemical synthesis and explosion shock synthesis. Detonation chemical synthesis is a process that uses the high temperature and high pressure generated by the explosion of energetic materials (such as explosives) to decompose and crystallize precursors into new products. It has the characteristics of strong work, fast reaction rate and high energy density; explosion shock synthesis is a process that uses the high temperature and high pressure environment caused by shock waves to decompose precursors into new substances. According to the CJ model (Chapman-Jouget theory) and the modified ZND model (Zeldocich NeumanDoring model) on this basis, the detonation wave can be regarded as composed of a chemical reaction zone and a front shock wave, which is closer to the actual reaction state. The explosion of energetic substances refers to the rapid conversion of its huge internal energy into heat and other releases in a very short time, and acts on the substance in a strong exothermic reaction. This process forms a huge jet shock wave, and can cause the reactants to generate molecular clusters, atomic groups and other small mass functional factors or gasification. When cooled in an inert environment, different active groups interact, precipitate, and fuse with each other, producing new nanoscale compounds.

[0012] The applicant's team has been researching absorbing materials for many years. Publication No. CN 114395371 B is a new research result obtained recently. The research result is to convert the copper-iron heteronuclear energetic complex {[CuFe3O(tza)6(H2O)3]·Cl·(NO3)2·4H2O} n After explosive decomposition in a closed reactor, calcination for 2 hours at a certain temperature in a nitrogen atmosphere can obtain nano- and micro-porous composite absorbers composed of Fe3O4, Fe4N, Cu, CuFe2O4, amorphous carbon and graphene. Although the total effective absorption bandwidth (the bandwidth with reflection loss less than -10dB) of this achievement covers 1.8-18GHz, the thickness corresponding to effective absorption in the range of 1.8-2.9GHz is about 4-5.5mm, and the corresponding reflection loss is about -15dB; this absorber material reaches the minimum reflection loss of -40.1dB at a high frequency of 16.3GHz (Ku band) and a thickness of 1.1mm, with a bandwidth of 3.2GHz.

[0013] Another research result published by this research team at the same time as CN 114395371 B was disclosed in CN114364242A. This research result specifically mentioned the zinc-iron heteronuclear energetic complex {[ZnFe3O(tza)6(H2O)3](NO3)3·5H2O} n After explosive decomposition at 280°C in a closed reactor, it is calcined at 650°C in a nitrogen atmosphere for 2h to obtain nano- and micron-sized composite powders composed of Fe, ZnO, Fe3O4, ZnFe2O4, amorphous carbon and graphene. This powder is mixed with paraffin at a mass ratio of 7:3 to obtain an absorbing material. The total bandwidth of the absorbing material obtained from this research result is 2.6-18GHz, but the band with reflection loss less than -30dB is 8-12GHz (X band), and the thickness at this time is 1.9-2.5mm.

[0014] By comparing the two recent research results of this research team, the reflection loss is also the smallest in the Ku and X bands, and the thickness of the minimum loss is substantially different. The thickness of the copper-iron complex at the minimum loss in the Ku band (-40.1dB) is only 1.1mm, while the thickness of the zinc-iron complex at the minimum loss in the X band (-37.9dB) is 2.4mm. In general, there are relatively few studies on absorbing materials for bands below 8GHz, and the performance of absorbing materials for C, S, L, X, and Ku bands needs to be improved. Therefore, it is imperative to develop an absorbing material that performs well in both low-frequency and high-frequency absorbing performance.

[0015] References: Pan JN, Yang HD, Hong Q, et al. Bimetal-organic frameworks derivedtuneable Co nanoparticles embedded in porous nitrogen-doped carbon nanorods as high-performance electromagnetic wave absorption materials [J]. Journal of Materials Chemistry C, 2021, 9: 7302-7308. Yu Y D,Fang Y,Hu Q,et al.Hollow MOF-derived CoNi / C composites aseffective electromagnetic absorbers in the X-band and Ku-band[J].Journal ofMaterials Chemistry C,2022,10:983-993.Qiang R,Du Y,Zhao H,Wang Y,Tian C,Li Z,Han X,Xu P,Metal organic framework-derived Fe / C nanocubes toward efficientmicrowave absorption,J.Mater.Chem.A.3(25)(2015)13426-13434. Ouyang J,He Z L,Zhang Y,et al.Trimetallic FeCoNi@C nanocompositehollow spheres derived from metal-organic frameworks with superiorelectromagnetic wave absorption ability[J].ACS Applied Materials&Interfaces,2019,11(42):39304-39314. Wei S,Shi Z,Li X,et al.Bimetallic MOF-derived CoFe@nitrogen-dopedcarbon composites for wide bandwidth and excellent microwave absorption[J].Journal of Alloys and Compounds:An Interdisciplinary Journal of MaterialsScience and Solid-state Chemistry and Physics,2022(910):164861. Yang HL, Zhang performance, Ceram.Int.47(2)(2021)2155-2164.https: / / doi.org / 10.1016 / j.ceramint.2020.09.053 Summary of the invention

[0016] Since the method for preparing the absorbing material of the present application is relatively environmentally friendly, simple, and has similar steps and processes, but is a typical representative of experimental disciplines, a slight error can lead to a huge mistake, so in order to clearly, completely and briefly describe the invention process of the present application, it is only described in a way that combines an explanatory or general description with examples of specific implementation methods.

[0017] In this application, the cobalt-iron based energetic metal organic complex is also referred to as CoFe-MOF.

[0018] The PXRD detection conditions in this application are as follows: the target material in the closed ceramic light tube (3kW) of the PXRD (Japan Rigaku, MiniFlex600) used in the experiment is a Cu target, and the characteristic rays are Suitable for testing inorganic substances. The voltage set during the test is 20kV, the test range is 5-90°, and the scanning rate is 10°·min -1 The test results were processed by XRD analysis software HighscorePlus and Jade 6.0, and then compared with the standard spectra in their own open crystal structure database (Crystallography Open Database, COD) and PDF database to identify the phase of the sample to be tested.

[0019] The SEM model used in this application is a bruker 6 / 30MERLIN Compact field emission electron microscope. A small amount of powder sample is fixed on the sample stage with conductive glue. To ensure good conductivity, the gold-plated sample is placed in the sample chamber and evacuated. After stabilization, the image of the sample can be collected.

[0020] The Raman spectrometer model used in this application is: a French HORIBA Scientific HREvolution Raman spectrometer was used to identify the structure and crystallinity of the sample, and the wave number of data collection was 50-4000cm-1 Within the range, the wavelength selected by the laser is 532nm, and the instrument starts running to collect spectra.

[0021] Model of vector network analyzer: Before testing using a vector network analyzer (Model E5071C, Agilent Technologies, USA), the target ratio of paraffin wax and the solid complex powder to be tested were mixed evenly at a temperature at which the organic binder could melt, and then taken out and solidified and melted again, and mixed evenly again, and this was repeated three times. Finally, the absorbing material was made into a coaxial ring that met the test requirements, and its absorbing performance was tested. The coaxial ring had an outer diameter of 7.00 mm, an inner diameter of 3.04 mm, and a thickness of 2.00 mm, which was set as required.

[0022] In the present application, Htza is tetrazolylacetic acid.

[0023] In the present application, the explosion-proof high temperature and high pressure resistant flange reactor is also referred to as flange reactor.

[0024] In this application, CoFe-X is used to represent the products obtained by calcining CoFe-MOF at different calcination temperatures. For example, CoFe-270, CoFe-300, CoFe-500, CoFe-600, CoFe-700, and CoFe-800 are used to represent the nano / micron-scale porous black carbon composite powders obtained by calcining CoFe-MOF at 270°C, 300°C, 500°C, 600°C, 700°C, and 800°C, respectively.

[0025] The calcination explosion temperature in this application refers to the temperature at which the flange reactor is placed in a muffle furnace at 10-20°C·min -1 The temperature is raised at a rate of 10000 ℃ until CoFe-MOF is melted, and the temperature is kept constant until an explosion is heard.

[0026] In order to enrich the types of low-frequency absorbing materials, provide more choices for production and life, and improve the absorbing performance of absorbing materials at low and high frequencies, the present application first provides an absorbing material with a corresponding reflection loss of about -30dB in the range of 3-5GHz and a thickness of 4-5.5mm, and a minimum RL value of -77.84dB and a bandwidth of 3.7GHz at a high frequency band of 11.36GHz and a thickness of 2.03mm. It not only enriches a kind of absorbing material with excellent reflection loss performance at low frequencies, but also provides an absorbing material with significantly improved high-frequency absorbing performance.

[0027] The wave absorbing material comprises CoFe-MOF ({[CoFe3O(tza)6(H2O)3](NO3)3·5H2O} n) is calcined until explosion to obtain a powder (also called CoFe-X) and an organic binder, the weight ratio of CoFe-X to the organic binder is 1:1, and the organic binder is paraffin or epoxy resin used as a wave-transmitting material.

[0028] The Fe-O bond length of the CoFe-MOF is in the range of arrive The bond angle of O-Fe-O ranges from 84.54 (14)° to 178.72 (16)°. The central Co2+ ion is a hexacoordinated octahedral structure, and the N1 atoms on the tetrazole rings of the six different ligands tza- Six coordinating atoms are contributed, and the N-Co-N bond angles range from 87.42(12)° to 180.0°.

[0029] The X in the CoFe-X is 260°C-800°C, wherein 260°C≤X≤300°C is the direct calcination temperature; the 300°C<X≤800°C is the staged calcination temperature, and the staged calcination temperature refers to heating X to 260°C≤X≤300°C and maintaining it until an explosion is heard, then cooling it, and then heating it to 300°C<X≤800°C and maintaining it for 2 hours or more.

[0030] 1. The powders obtained by calcining the CoFe-MOF at 260°C≤X≤300°C are recorded as CoFe-260 to CoFe-300. The XRD patterns of the CoFe-260 to CoFe-300 have diffraction peaks at 2θ=37.8°, 45.8° and 45.1° corresponding to the (021), (121) and (103) crystal planes of the standard diffraction card of Fe3C (ICSD code 060688), indicating the presence of Fe3C in the product; the diffraction peaks at 2θ=38.1°, 41.2° and 43.6° correspond to the (110), (002) and (111) crystal plane diffraction peaks of the standard diffraction card of Fe3N (ICSD code 079982), indicating the presence of Fe3N in the product; the diffraction peaks at 2θ=35.4° and 43.1° correspond to the standard diffraction card of CoFe2O4 (ICSD code 039131), indicating the presence of CoFe2O4 in the product; the diffraction peak at 2θ=43.8° corresponds to the (111) crystal plane diffraction peak of the standard diffraction card of C (COD code 2101499), indicating the presence of C in the product.

[0031] The powders obtained by calcining the CoFe-MOF at 300°C<X≤800°C are respectively recorded as CoFe-300 to CoFe-800. The diffraction peaks at 2θ=44.8°, 65.2° and 82.5° of the XRD spectra of the CoFe-300 to CoFe-800 correspond to the (110), (200) and (211) crystal planes of the standard diffraction card of CoFe (COD code 9004229), indicating the presence of CoFe in the product; the diffraction peaks at 2θ=44.8°, 65.2° and 82.5° correspond to the (110), (200) and (211) crystal plane diffraction peaks of the standard diffraction card of Fe (ICSD code 9006595), indicating the presence of Fe in the product.

[0032] The Raman spectra of CoFe-X are respectively at 1350 cm -1 and 1585cm -1 It has characteristic peaks, namely D peak and G peak, whose intensity ratio is I D / I G At 1.02-1.05.

[0033] The 2D peak of the Raman spectrum of CoFe-X is located at 2700 cm -1 Nearby, the 2D peak is also called G' peak, and the ratio of the G peak intensity to the 2D peak intensity is greater than 1.0.

[0034] Secondly, the present application provides a method for preparing an absorbing material, the preparation method comprising preparing CoFe-MOF and calcining to obtain CoFe-X, wherein the organic binder is paraffin or an epoxy resin that can be used as a wave-transmitting material.

[0035] The preparation steps of the CoFe-MOF include: 3+ 、Co 2+ CoFe-MOF was prepared by reaction in an alkaline aqueous solution with pH=8.0-10.0, wherein Htza, Fe 3+ and Co 2+ The molar ratio is between 3:1:1 and 5:1:2, including the endpoint values; In a specific embodiment, the preparation steps of CoFe-MOF are as follows: 30 ml of pure water is added with NaOH solution (0.01 mol·L -1) adjust the pH to 8.0-10.0, continue to add 1.2mmol Htza and 0.4mmol FeCl3·6H2O until they are completely dissolved, then heat and stir in a constant temperature water bath at 70-95°C until the solution color deepens, about 0.5 hour, add 0.4mmol Co(NO3)3·6H2O and continue to heat and stir until a small amount of precipitation is precipitated, about 1.0 hour, cool the solution, filter the filtrate, and after about 5 days at room temperature, blocky red-brown crystals are generated. The product molecular formula is {[CoFe3O(tza)6(H2O)3](NO3)3·5H2O} n In actual operation, due to the influence of the pH of the solution and the hydrolysis equilibrium of the compound, the compounds in the solution will not react completely in the ideal ratio in the molecular formula to generate compounds, so there will always be excess reactants to ensure that the excess reactants can fully react. Those skilled in the art can achieve the molar ratio of Htza to FeCl3·6H2O and Co(NO3)3·6H2O according to Htza, FeCl3·6H2O and Co(NO3)3·6H2O through the above steps without creative labor. 3+ and Co 2+ The ratio of Htza:Fe:Co is in the range of 3:1:1 to 5:1:2, and the absorbing material claimed in this application is produced; in some specific embodiments, the molar ratio of Htza:Fe:Co is 3:1:1; In some specific embodiments, the molar ratio of Htza:Fe:Co is 4:1:1; In some specific embodiments, the molar ratio of Htza:Fe:Co is 5:1:1; In some specific embodiments, the molar ratio of Htza:Fe:Co is 5:1:2; In some specific embodiments, the base or strong base weak acid salt used to adjust the pH is ammonia water or sodium acetate, and the pH of the reaction solution is adjusted to be within the range of 8.0-10.0; In some embodiments, the pH of the alkaline solution is 8.0, 8.5, 9.0, 9.5, 10.0; In some embodiments, the temperature of the thermostatic water area is 70°C, 72°C, 75°C, 78°C, 80°C, 85°C, 90°C, 95°C; In some embodiments, the mixture is heated and stirred in a constant temperature water bath for 0.5 h, 1 h, 1.5 h, and after adding Co(NO3)3·6H2O, the heating and stirring are continued for 1.0, 1.5, 2.0, 2.5 h.

[0036] The calcination step includes direct calcination and staged calcination. The direct calcination is to convert {[CoFe3O(tza)6(H2O)3](NO3)3·5H2O} nPut it into an explosion-proof high temperature and high pressure resistant flange reactor (25mL, ≤550℃, ≤20MPa), hereinafter referred to as flange reactor, and place the flange reactor in a muffle furnace at 10-20℃·min -1 The temperature is heated at a rate of 10000 to a temperature above the melting temperature of CoFe-MOF, and the temperature is kept at this temperature until an explosion is heard, the power of the muffle furnace is turned off to stop heating and the furnace is allowed to cool naturally to room temperature. Then the nano / micron-scale porous black carbon composite powder generated by the explosion is collected; In some direct calcination embodiments, the nano / micron-scale porous black carbon composite powder obtained by explosive decomposition of CoFe-MOF at holding temperatures of 260°C, 270°C, and 300°C is also referred to as CoFe-X, and is labeled as CoFe-260, CoFe-270, and CoFe-300, respectively; In some embodiments of staged calcination, the CoFe-X obtained by direct calcination is cooled to room temperature and then placed in a porcelain boat, which is then placed in a tube furnace for calcination. In order to exhaust the air, N2 is passed for 10 to 30 minutes before heating, and the heating rate is set to 3 to 6 ° C. min -1 , then under N2 protection, the temperature was raised from room temperature to 500℃, 600℃, 700℃, and 800℃, respectively, and calcined for 2h. Then it was naturally cooled to room temperature, and the products were collected and named CoFe-500, CoFe-600, CoFe-700, and CoFe-800, respectively.

[0037] CoFe-X is mixed with an organic binder in a mass ratio of 1:1 to obtain an absorbing material. The organic binder is paraffin or an epoxy resin used as a wave-transmitting material. The specific mixing method is as follows: the paraffin wax and the solid composite powder to be tested in a target ratio are mixed evenly at 80°C, and after solidification, they are heated at 80°C until the paraffin melts, and then mixed evenly again. This is repeated three times to finally produce a coaxial ring with an outer diameter of 7.00 mm, an inner diameter of 3.04 mm, and a thickness of 2.00 mm.

[0038] The electromagnetic parameters of the absorbing material are measured by a vector network analyzer; the product is also characterized by a powder X-ray diffractometer (PXRD), a scanning electron microscope (SEM), a Raman spectrometer (Raman), a vector network analyzer (VNA), etc. In some specific embodiments, paraffin is replaced by a wave-transmitting material that can be used as a binder, such as an epoxy resin.

[0039] The 80°C represents the temperature at which the paraffin is melted when the binder is paraffin. Therefore, if epoxy resin is used instead, the 80°C here can be selected based on the melting point of the epoxy resin. For example, in a specific embodiment, the epoxy resin is Epikote 828 from RESOLUTION (formerly SHELL), the ratio of CoFe-X to epoxy resin is 1:1, and the mixing temperature is 45-50°C.

[0040] In a specific embodiment of staged calcination, the molar ratio of Htza:Fe:Co is 3:1:1, and the temperature is kept at 270°C at which an explosion sound is heard and the calcination temperature is 500°C to obtain CoFe-500; the absorbing material composed of CoFe-500 and paraffin in a weight ratio of 1:1 has a maximum loss of -51.50 dB at 3.25 GHz and a thickness of 5.10 mm; the maximum effective absorption bandwidth is 4.46 GHz at a thickness of 1.3 mm; the total effective absorption bandwidth in the frequency range of 1-18 GHz and a thickness of 1.00-5.50 mm can reach 2.42-18 GHz.

[0041] In a specific implementation scheme of staged calcination, the molar ratio of Htza:Fe:Co is 3:1:1, and the temperature at which the explosion is heard is 270°C and the calcination temperature is 600°C to obtain CoFe-600; the absorbing material composed of CoFe-600 and paraffin in a weight ratio of 1:1 has a maximum loss of -26.58dB at 3.60GHz; the thickness is 4.50mm; the total effective absorption bandwidth in the range of 1-18GHz and 1.00-5.50mm can reach 2.32-18GHz; and when the calcination conditions are the same, but the molar ratio of Htza:Fe:Co is different, for example, the molar ratios of Htza:Fe:Co are 4:1:1, 5:1:1 and 5:1:2 respectively, the calcination method is the same as the molar ratio of Htza:Fe:Co is 3:1:1, that is, when the temperature at which the explosion is heard is 270°C and the calcination temperature is 600°C, the performance of the obtained absorbing material is the same.

[0042] In a specific embodiment of staged calcination, the molar ratio of Htza:Fe:Co is 5:1:1, the temperature of the explosion is 270°C, and the calcination temperature is 700°C; the absorbing material composed of CoFe-700 and paraffin wax with a weight ratio of 1:1 has a maximum loss of -56.88dB at 3.99GHz; a thickness of 5.00mm; a maximum loss of -77.84dB at 11.36GHz; a thickness of 2.03mm; and a total effective absorption bandwidth of 2.90-18GHz. At this calcination temperature, the molar ratios of Htza:Fe:Co were also investigated at 4:1:1, 5:1:1 and 5:1:2, respectively. The calcination method was the same as that of the molar ratio of Htza:Fe:Co being 3:1:1, that is, when the temperature of the explosion is 270°C and the calcination temperature is 700°C, the performance of the obtained absorbing material is the same.

[0043] In a specific embodiment of staged calcination, the molar ratio of Htza:Fe:Co is 4:1:1, the temperature of the explosion is 270°C, and the calcination temperature is 800°C; the absorbing material composed of CoFe-800 and paraffin with a weight ratio of 1:1 has a maximum loss of -20.68dB at 17.92GHz; the thickness is 5.50mm, and the corresponding effective absorption bandwidth is 2.69GHz. At this calcination temperature, the molar ratios of Htza:Fe:Co are also investigated at 4:1:1, 5:1:1 and 5:1:2, respectively. The calcination method is the same as that of the molar ratio of Htza:Fe:Co is 3:1:1, that is, when the temperature of the explosion is 270°C and the calcination temperature is 800°C, the performance of the obtained absorbing material is the same.

[0044] In a direct calcination specific embodiment, the molar ratio of Htza:Fe:Co is 5:1:2, and the temperature at which the explosion is heard is 270°C. The absorber composed of CoFe-270 and epoxy resin in a ratio of 1:1 has a maximum loss of -51.65dB at 4.28GHz; a thickness of 4.8mm; and a total effective absorption bandwidth of 3.18-18GHz in the range of 1-18GHz and a thickness of 1.0-5.5mm. At this calcination temperature, the molar ratios of Htza:Fe:Co were also investigated at 4:1:1, 5:1:1 and 5:1:2, respectively. The calcination method was the same as that of the molar ratio of Htza:Fe:Co of 3:1:1, that is, the absorber obtained by heating to a temperature of 270°C at which the explosion was heard had the same performance.

[0045] In a specific embodiment of direct calcination, the molar ratio of Htza:Fe:Co is 3:1:1, the temperature at which the explosion sound is heard is 260°C and 300°C, the absorbing material is composed of CoFe-X and paraffin in a ratio of 1:1, and the time of insulation until the explosion is different at 260°C, 270°C, and 300°C, but the products are the same. Specifically, the insulation time at 260°C is about 35 minutes, the insulation time at 270°C is about 15 minutes, and the insulation time at 300°C is about 10 minutes. The three temperatures all explode during the insulation time, and the calcination is stopped immediately after the explosion occurs, and the products are cooled to room temperature, and the explosion products are the same.

[0046] In some specific embodiments, the applicant also investigated the type of binder in the absorbing material and the ratio of CoFe-X to the binder. The results showed that epoxy resin and paraffin wax can be used as wave-transmitting materials in the organic binder, and when the weight ratio with CoFe-X is 1:1, the obtained absorbing material is similar to the absorbing material described in the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Attached Figure 1 Co in CoFe-MOF 2+ and Fe 3+ The coordination mode of Attached Figure 2 Fe in CoFe-MOF 3+ Coordination pattern diagram of ions; Attached Figure 3 Co in CoFe-MOF 2+ Coordination structure diagram of Attached Figure 4 XRD pattern of explosion products at 270 °C; Attached Figure 5 Raman spectrum of explosion products at 270°C; Attached Figure 6 SEM image of CoFe-270 powder under low magnification; Attached Figure 7 SEM image of CoFe-270 powder under high magnification; Attached Figure 8 XRD patterns of products calcined at 600°C, 700°C, and 800°C, i.e., XRD patterns of CoFe-600, CoFe-700, and CoFe-800; Attached Fig. 9 Raman spectra of the products at staged calcination temperatures of 600°C, 700°C, and 800°C, i.e., Raman spectra of CoFe-600, CoFe-700, and CoFe-800; Attached Fig.10 SEM image of CoFe-700 powder under low magnification; Attached Fig.11 SEM image of CoFe-700 powder under high magnification; Attached Fig.12 Reflection loss of a mixture of explosion products and paraffin at 270°C (1:1) versus frequency and thickness; Attached Fig.13 Reflection loss of CoFe-600 and paraffin mixture (1:1) as a function of frequency and thickness; Attached Fig.14 Reflection loss of CoFe-700 and paraffin mixture (1:1) as a function of frequency and thickness; Attached Fig.15 Reflection loss of CoFe-800 and paraffin mixture (1:1) as a function of frequency and thickness; Attached Fig.16 Impedance matching of the mixtures (1:1) of different powders CoFe-270, CoFe-600, CoFe-700 and CoFe-800 with paraffin wax | Z in / Z0|; Attached Fig.17 The curve of the tangent loss value of CoFe-270 changing with frequency; Attached Fig.18 The variation curve of tangent loss value of CoFe-500 with frequency; Attached Fig.19 The variation curve of tangent loss value of CoFe-600 with frequency; Attached Fig. 20 The curve of the tangent loss value of CoFe-700 changing with frequency; Attached Fig.21 The curve of the tangent loss value of CoFe-800 changing with frequency. DETAILED DESCRIPTION

[0048] The preparation of CoFe-MOF, the method of calcining CoFe-MOF to obtain CoFe-X, and the process of mixing CoFe-X with a binder to obtain the final absorbing material in the present application are similar and easy to understand for those skilled in the art. In the background technology and invention content, the applicant believes that it is sufficient to explain the selection and ratio of metal and organic complex in the energetic metal organic complex, the influence of explosion temperature and calcination temperature on the absorbing material. Therefore, the specific implementation method only shows that the performance of the absorbing material can be achieved within the range of various parameters described in the present application, and does not represent the entire process of the entire invention discovery.

[0049] Preparation Example Preparation of CoFe-MOF Preparation Example 1.1 Take 30 ml of pure water and add NaOH solution (0.01 mol·L -1 ) adjust the pH to 8.0-10.0, continue to add 1.2mmol of Htza and 0.4mmol of FeCl3·6H2O until they are completely dissolved, then heat and stir in a constant temperature water bath at 80°C until the solution color deepens, which is about 0.5 hour, add 0.4mmol of Co(NO3)3·6H2O and continue to heat and stir until a small amount of precipitation is precipitated, which is about 1.0 hour, and the solution is cooled to room temperature and filtered. The filtrate precipitates blocky red-brown crystals at room temperature, which is the product CoFe-MOF, having the following molecular formula {[CoFe3O(tza)6(H2O)3](NO3)3·5H2O} n .

[0050] Preparation Examples 1.2-1.4 The difference from Preparation Example 1.1 is that the molar ratios of Htza:Fe:Co are 4:1:1, 5:1:1 and 5:1:2 respectively; the water bath temperatures are 70°C, 95°C and 85°C respectively. The obtained products can all be represented by CoFe-MOF, and the molecular formula is {[CoFe3O(tza)6(H2O)3](NO3)3·5H2O} n .

[0051] Co in CoFe-MOF obtained in the preparation example 2+ and Fe 3+ The coordination mode is shown in the attached Figure 1 As shown; Fe in CoFe-MOF 3+ The coordination mode of the ion is as follows Figure 2 As shown; Co in CoFe-MOF 2+ The coordination structure is shown in Figure 3 shown.

[0052] Example 1 Preparation of CoFe-X by direct calcination Example 1.1 Preparation of CoFe-270 Example 1.1.1 The CoFe-MOF obtained in Preparation Example 1.1 was placed in an explosion-proof, high-temperature and high-pressure resistant flange reactor (25 mL, ≤550°C, ≤20 MPa), hereinafter referred to as the flange reactor. The flange reactor was placed in a muffle furnace at 10-20°C·min -1 The temperature was raised to 270°C at a rate of 100°C and kept at 270°C until an explosion sound was heard. The holding time was about 15 minutes. The power of the muffle furnace was turned off to stop heating and the furnace was allowed to cool naturally to room temperature. The nano / micron-scale porous black carbon composite powder generated by the explosion was then collected.

[0053] Examples 1.1.2-1.1.4 The difference from Example 1.1.1 is that the CoFe-MOF of Preparation Examples 1.2-1.4 are calcined according to the method of Example 1.1.1 respectively. Since the XRD, Raman spectrum, SEM and the absorbing properties of the absorbing material composed of the organic binder in a weight ratio of 1:1 obtained by the calcination method of Example 1.1 are also similar, in this example, the calcined explosion products obtained in Example 1.1.1 are all represented by CoFe-270, and the calcined products obtained in the following examples are all recorded according to this method.

[0054] The XRD pattern of CoFe-270 is shown in the attached Figure 4 The Raman spectrum of the explosion product calcined at 270°C is shown in the attached figure. Figure 5 ; The SEM image of CoFe-270 powder under low magnification is shown in the attached Figure 6 ; SEM images of CoFe-270 powder under high magnification are shown in the attached figure Figure 7 .

[0055] The XRD diffraction peaks of the CoFe-270 at 2θ=37.8°, 45.8° and 45.1° correspond to the (021), (121) and (103) crystal planes of the standard diffraction card (ICSD code 060688) of Fe3C, indicating the presence of Fe3C in the product; the diffraction peaks at 2θ=38.1°, 41.2° and 43.6° correspond to the (110), (002) and (111) crystal plane diffraction peaks of the standard diffraction card (ICSD code 079982) of Fe3N, indicating the presence of Fe3N in the product; the diffraction peaks at 2θ=35.4° and 43.1° correspond to the standard diffraction card (ICSD code 079982) of CoFe2O4, indicating the presence of Fe3N in the product. 039131) indicates the presence of CoFe2O4 in the product; the diffraction peak at 2θ = 43.8° corresponds to the (111) diffraction peak of the standard diffraction card of C (COD code 2101499), indicating the presence of C in the product. Therefore, CoFe-270 contains the following composition: Fe3C / Fe3N / CoFe2O4 / C.

[0056] Example 1.2 Preparation of CoFe-260 The difference from Example 1.1 is that the calcination explosion temperature of Examples 1.2.1-1.2.4 is 260°C, and the explosion sound is heard after keeping at 260°C for about 35 minutes. The obtained product is recorded as CoFe-260.

[0057] Example 1.3 Preparation of CoFe-300 The difference from Example 1.1 is that the calcination explosion temperature of Examples 1.3.1-1.3.4 is 300°C, and the explosion sound is heard after keeping at 300°C for about 10 minutes. The obtained product is recorded as CoFe-300.

[0058] Taking the SEM image of CoFe-270 obtained by the explosion method as an example, it can be seen that the surface of the product obtained by calcination and explosion at this temperature has an obvious porous structure and aggregates of nano / micron particles. It can be seen that the explosion method is one of the effective methods for obtaining nano / micron particles. In addition, the porous structure is not only conducive to the multiple reflection and scattering of electromagnetic waves, but also conducive to the loss of electromagnetic waves, and also conducive to reducing the density of the powder.

[0059] Example 2 Preparation of CoFe-X by staged calcination Here, only the secondary calcination of CoFe-270 obtained in Example 1.1.1 is taken as an example for detailed discussion, and other examples are briefly described or explained in the form of results.

[0060] The CoFe-270 was cooled to room temperature, then placed in a porcelain boat and calcined in a tube furnace. To exhaust all the air, N2 was passed through for 10 to 30 minutes before heating. The heating rate was set at 3 to 6 °C min. -1 , then under N2 protection, the temperature was raised from room temperature to 500℃, 600℃, 700℃, and 800℃, respectively, and calcined for 2h. Then it was naturally cooled to room temperature, and the products were collected and named CoFe-500, CoFe-600, CoFe-700, and CoFe-800, respectively.

[0061] The XRD spectra of the products calcined at 600°C, 700°C, and 800°C, i.e., the XRD spectra of CoFe-600, CoFe-700, and CoFe-800 are shown in the attached figure. Figure 8 The Raman spectra of the products at the staged calcination temperatures of 600°C, 700°C, and 800°C, namely, the Raman spectra of CoFe-600, CoFe-700, and CoFe-800 are shown in the attached figure. Fig. 9 As shown; the SEM image of CoFe-700 powder under low magnification is shown in the attached Fig.10 As shown; the SEM image of CoFe-700 powder under high magnification is shown in the attached Fig.11 shown.

[0062] Taking the scanning electron microscope (SEM) image of CoFe-700 as an example and comparing it with the SEM of CoFe-270 powder, the following conclusions can be drawn: after staged high-temperature calcination, the particle size becomes larger, and a porous structure and nano / micron particles are clearly visible on the surface of the powder. It can be seen that porous nano / micron powders can be obtained by taking the particles generated after the calcination explosion as the precursor and calcining them again at high temperature.

[0063] The powders obtained by calcining the CoFe-MOF at 600°C, 700°C and 800°C are respectively recorded as CoFe-600, CoFe-700 and CoFe-800. The XRD diffraction peaks of CoFe-600, CoFe-700 and CoFe-800 at 2θ=44.8°, 65.2° and 82.5° correspond to the (110), (200) and (211) crystal planes of the standard diffraction card of CoFe (COD code 9004229), indicating the presence of CoFe in the product; the diffraction peaks at 2θ=44.8°, 65.2° and 82.5° correspond to the (110), (200) and (211) crystal plane diffraction peaks of the standard diffraction card of Fe (ICSDcode 9006595), indicating the presence of Fe in the product. Raman spectroscopy proves the presence of carbon materials. Therefore, CoFe-600, CoFe-700 and CoFe-800 all contain CoFe / Fe / C composition.

[0064] Example 3 Preparation of absorbing material The absorbing material is obtained by uniformly mixing CoFe-X and an organic binder. The specific mixing method is to uniformly mix the target ratio of paraffin and the solid complex powder to be tested at a temperature at which the organic binder can melt, take it out and solidify it, then melt it, mix it again, and finally make the absorbing material into a coaxial ring that meets the test requirements to test its absorbing performance. The coaxial ring has an outer diameter of 7.00 mm, an inner diameter of 3.04 mm, and a thickness of 2.00 mm.

[0065] The adhesives examined include paraffin wax and epoxy resin that can be used as a wave-transmitting material; some ratios thereof are also examined, including 1.07:1, 1:1, and 1:1.1.

[0066] Performance Testing 1. Reflection loss detection: Before testing with a vector network analyzer (E5071C model, Agilent Technologies, USA), the sample was mixed with paraffin wax in a weight ratio of 1:1, and the coaxial method was used for testing. The test range was 1-18GHz. The specific mixing method was to mix the target ratio of paraffin wax and the solid complex powder to be tested evenly at a temperature at which the organic binder can melt, take it out and solidify it, then melt it, mix it evenly again, and finally make the absorbing material into a coaxial ring that meets the test requirements to test its absorbing performance. The coaxial ring has an outer diameter of 7.00mm, an inner diameter of 3.04mm, and a thickness of 2.00mm.

[0067] 2. Tangent loss detection and impedance matching detection: Tangent loss and impedance matching are both simulated and calculated based on the data measured by reflection loss.

[0068] During simulation calculation, the thickness parameter settings are 1.00, 1.30, 1.40, 1.50, 1.60, 1.70, 2.00, 2.03, 2.30, 2.50, 3.00, 3.50, 4.00, 4.50, 4.80, 5.00, 5.10, and 5.50 respectively.

[0069] The reflection loss of the absorber obtained by mixing CoFe-270 and paraffin (1:1) with frequency and thickness is shown in the attached figure. Fig.12 As shown, the results show that this absorbing material reaches a minimum RL value of -51.65dB at a frequency of 4.28GHz and a thickness of 4.80mm, that is, it can effectively absorb more than 99.999% of the incident electromagnetic waves under this condition, and the effective absorption bandwidth at this thickness reaches 1.14GHz. The maximum effective absorption bandwidth is 3.39GHz at a thickness of 1.50mm. The total effective absorption bandwidth in the range of 1-18GHz and 1.00-5.50mm can reach 3.18-18GHz, and the low-frequency loss capacity is strong.

[0070] The reflection loss of the absorber obtained by mixing CoFe-600 and paraffin (1:1) with frequency and thickness is shown in the attached figure. Fig.13 As shown, it can be seen that this absorbing material reaches the minimum RL value of -26.58dB at a frequency of 3.60GHz and a thickness of 4.50mm, that is, under this condition, it can effectively absorb more than 99% of the incident electromagnetic waves (in the civilian aspect, people may not be aware of electromagnetic radiation enough, but electromagnetic radiation is very harmful to the immune system, etc. If the radiation protection effect is better, it is more beneficial to the human body; the military aspect is more precise. If the absorbing material can absorb more electromagnetic waves, the radar will not be able to detect the fighter, and the combat performance of the "stealth fighter" will be achieved, and the combat capability will be improved). The effective absorption bandwidth at this thickness is 1.43GHz. The maximum effective absorption bandwidth is 4.95GHz at a thickness of 1.40mm. The total effective absorption bandwidth in the range of frequency 1-18GHz and thickness 1.00-5.50mm can reach 2.32-18GHz, and the loss capacity is relatively strong.

[0071] The reflection loss of the absorber obtained by mixing CoFe-700 and paraffin (1:1) with frequency and thickness is shown in the attached figure. Fig.14As shown, it can be seen that the RL value of this absorbing material reaches -56.88dB at a low frequency of 3.99GHz and a thickness of 5.00mm, that is, under this condition, it can effectively absorb more than 99.999% of the incident electromagnetic waves, and the effective absorption bandwidth at this thickness reaches 1.51GHz. The maximum effective absorption bandwidth reaches 4.06GHz at a thickness of 2.00mm. The minimum RL value of -77.84dB is reached at a high frequency of 11.36GHz and a thickness of 2.03mm, so it has excellent absorbing performance at both low and high frequencies. The total effective absorption bandwidth in the frequency range of 1-18GHz and the thickness range of 1.00-5.50mm can reach 2.90-18GHz, with the strongest loss capacity and high temperature resistance. This absorbing material has a minimum reflection loss of -56.88dB in the low frequency range of 3-5GHz, and the RL value at the high frequency of 11.36GHz is significantly reduced compared with the prior art.

[0072] The reflection loss of the absorber obtained by mixing CoFe-800 and paraffin (1:1) with frequency and thickness is shown in the attached figure. Fig.15 As shown, it can be seen that the minimum RL value of -20.68dB is reached at a frequency of 17.92GHz and a thickness of 5.5mm, that is, under this condition, more than 99% of the incident electromagnetic waves can be effectively absorbed. The effective absorption bandwidth at this thickness reaches 2.69GHz, and the loss capacity is weaker than that of the sample CoFe-700.

[0073] Impedance matching of CoFe-270, CoFe-600, CoFe-700 and CoFe-800 mixed with paraffin wax (1:1) |Z in / Z0|Test results are as attached Fig.16 As shown in the attached Fig.16 The test results show that the impedance matching values ​​of samples CoFe-270 and CoFe-700 are both 0.99, and the impedance matching value of sample CoFe-600 is 0.91. The closer the impedance matching value is to 1.0, the better the impedance matching is, and the more electromagnetic waves are incident into the material, so the impedance matching characteristics of samples CoFe-270 and CoFe-700 are relatively good.

[0074] Attached Fig.17 , 18 , 19, 20 and 21 are the tangent loss values ​​of samples CoFe-270, CoFe-500, CoFe-600, CoFe-700 and CoFe-800 respectively. It can be seen that the magnetic loss tangent value tanδ of sample CoFe-270 in the frequency range of 1-13.71 GHz is μ Greater than the dielectric loss tangent tanδ ε , indicating that the magnetic loss mechanism is dominant in this frequency range, and the effects of magnetic loss and dielectric loss are not much different in the range of 13.71-18 GHz. Fig.18 , Fig.19 , Fig. 20 , Fig.21 The magnetic loss tangent tanδ of samples CoFe-500, CoFe-600, CoFe-700 and CoFe-800 is within the frequency range of 1-18 GHz. μ Greater than the dielectric loss tangent tanδ ε , indicating that the magnetic loss mechanism is dominant in the entire frequency range.

[0075] The type of binder in the absorbing material and the ratio of CoFe-X to the binder. The results show that epoxy resin and paraffin can be used as wave-transmitting materials among organic binders. The ratio of CoFe-X to the binder requires to be relatively precise. Therefore, when the organic binder is selected from epoxy resin and paraffin, and the weight ratio with CoFe-X is 1:1, the obtained absorbing material is similar to the absorbing material described in the present application.

[0076] The Raman spectra of CoFe-X obtained in Examples 1 and 2 both have two significant peaks, at 1350 cm -1 and 1585cm -1 Nearby, there are two characteristic peaks D and G belonging to carbon materials, and their intensity ratio is I D / I G The value of indicates the degree of defects and graphitization of the material itself. Due to the I D / I G The values ​​are 1.02, 1.05, 1.04 and 1.03 respectively, indicating that the degree of graphitization inside the powder after the explosion increases with the increase of the calcination temperature in the tubular furnace. The external factor affecting the degree of graphitization of carbon materials is mainly temperature, but the length of residence time at high temperature also plays a certain role. The higher the graphitization temperature, the shorter the time to enter the stable state of graphitization (the interlayer spacing no longer changes significantly). However, when graphitizing at a lower temperature, it takes a long time to reach a similar stable state. The higher the heating temperature, the lower the resistivity, the closer the adjacent crystal layer spacing is to the ideal graphite crystal of 0.3354nm, and the higher the degree of graphitization. There is also a certain relationship between the degree of graphitization and the residence time at high temperature. The higher the graphitization temperature, the shorter the time required to enter the stable state of graphitization, the longer the insulation time, the lower the resistivity, and the higher the degree of graphitization. In addition, pressurization has a significant promoting effect on graphitization, such as the high temperature and high pressure generated at the moment of explosion. And the internal structural defects of CoFe-X and I D / I GThe graphitization degree mainly affects the dielectric constant of carbon composite materials, which in turn affects the impedance matching. The disordered vibration of the lattice escapes from the center of the Brillouin zone, forming a structural defect, which is manifested as the appearance of the D peak, while the appearance of the G peak is due to the sp 2 The Raman spectrum of single-layer graphene is 2900cm -1 The intensity of the 2D peak near is stronger than that of the G peak, while the 2D peak intensities of CoFe-270, CoFe-600, CoFe-700 and CoFe-800 prepared in this paper are all weaker than the G peak, that is, the ratio of the G peak intensity to the 2D peak intensity is greater than 1.0, indicating that the C in CoFe-270, CoFe-600, CoFe-700 and CoFe-800 is not single-layer graphene, but multi-layer graphene and amorphous carbon.

[0077] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A wave absorbing material, characterized in that: The invention comprises CoFe-X and an organic binder in a weight ratio of 1:1, wherein the CoFe-X is composed of a material having the following molecular formula {[CoFe3O(tza)6(H2O)3](NO3)3·5H2O} n The CoFe-MOF is obtained by calcining, wherein X represents the calcination temperature; the organic binder is paraffin or epoxy resin used as a wave-transmitting material.

2. The absorbing material according to claim 1, characterized in that: The Fe-O bond length of the CoFe-MOF is in the range of 1.9124(8) Å to 2.065(4) Å, and the O-Fe-O bond angle is in the range of 84.54(14)° to 178.72(16)°. 2+ The ion is a hexacoordinated octahedral structure with six different ligands tza - The N1 atom on the tetrazole ring [Co1-N1 = 2.144(3) Å] contributes six coordinated atoms, and the N-Co-N bond angle ranges from 87.42(12)° to 180.0°.

3. The absorbing material according to claim 1, characterized in that: The X in the CoFe-X is 260°C-800°C, wherein 260°C≤X≤300°C is the direct calcination temperature; the 300°C<X≤800°C is the staged calcination temperature, and the staged calcination temperature refers to heating X to 260°C≤X≤300°C and maintaining it until an explosion is heard, then cooling it, and then heating it to 300°C<X≤800°C and maintaining it for 2 hours or more.

4. The absorbing material according to claim 3, characterized in that: The powders obtained by calcining the CoFe-MOF at 260°C≤X≤300°C are recorded as CoFe-260 to CoFe-300. The XRD patterns of the CoFe-260 to CoFe-300 have diffraction peaks at 2θ = 37.8°, 45.8° and 45.1° corresponding to the (021), (121) and (103) crystal planes of the standard diffraction card of Fe3C (ICSD code 060688), indicating the presence of Fe3C in the product; the diffraction peaks at 2θ = 38.1°, 41.2° and 43.6° correspond to the (110), (002) and (111) crystal plane diffraction peaks of the standard diffraction card of Fe3N (ICSD code 079982), indicating the presence of Fe3N in the product; the diffraction peaks at 2θ = 35.4° and 43.1° correspond to the standard diffraction card of CoFe2O4 (ICSD code039131), indicating the presence of CoFe2O4 in the product; the diffraction peak at 2θ = 43.8° corresponds to the (111) diffraction peak of the standard diffraction card of C (COD code 2101499), indicating the presence of C in the product.

5. The absorbing material according to claim 3, characterized in that: The powders obtained by calcining the CoFe-MOF at 300°C<X≤800°C are respectively recorded as CoFe-300 to CoFe-800. The diffraction peaks at 2θ=44.8°, 65.2° and 82.5° of the XRD spectra of the CoFe-300 to CoFe-800 correspond to the (110), (200) and (211) crystal planes of the standard diffraction card of CoFe (COD code 9004229), indicating the presence of CoFe in the product; the diffraction peaks at 2θ=44.8°, 65.2° and 82.5° correspond to the (110), (200) and (211) crystal plane diffraction peaks of the standard diffraction card of Fe (ICSD code 9006595), indicating the presence of Fe in the product.

6. The absorbing material according to claim 1, characterized in that: The Raman spectra of CoFe-X are respectively at 1350 cm -1 and 1585 cm -1 It has characteristic peaks, namely D peak and G peak, whose intensity ratio is I D / I G At 1.02-1.

05.

7. The absorbing material according to claim 1, characterized in that: The 2D peak of the Raman spectrum of CoFe-X is located at 2700 cm -1 Nearby, the 2D peak is also called G' peak, and the ratio of the G peak intensity to the 2D peak intensity is greater than 1.

0.

8. A method for preparing the absorbing material according to claim 1-7, comprising the steps of preparing and calcining CoFe-MOF, characterized in that: The preparation steps of the CoFe-MOF include tetrazolylacetic acid, Fe 3+ 、Co 2+ CoFe-MOF is prepared by reacting in an alkaline aqueous solution with a pH of 8.0-10.

0. The tetraacetic acid is also called Htza, wherein Htza, Fe 3+ and Co 2+ The molar ratio is between 3:1:1 and 5:1:2, including the endpoint values; the temperature of the calcining step is 260°C≤X≤800°C.

9. The preparation method according to claim 8, characterized in that: The calcination is a staged calcination or a direct calcination. The staged calcination is to first calcine CoFe-MOF to 260°C≤X≤300°C until an explosion is heard, cool to room temperature, and then calcine again at 300°C<X≤800°C to obtain CoFe-X; the direct calcination is to calcine CoFe-MOF at 260°C≤X≤300°C until an explosion is heard, cool to room temperature, and obtain CoFe-X.

Citation Information

Patent Citations

  • Porous composite wave-absorbing agent based on zinc-iron complex derivation and preparation method of porous composite wave-absorbing agent

    CN114364242A

  • A composite microwave absorber derived from a tetrazolium-copper-iron tetrazolium acetate complex and its preparation method

    CN114395371B